Congenital eye anomalies: More mosaic than thought?. (21st August 2018) - Ohuchi, Hideyo; Sato, Keita; Habuta, Munenori; Fujita, Hirofumi; Bando, Tetsuya
Abstract : The eye is a sensory organ that primarily captures light and provides the sense of sight, as well as delivering non‐visual light information involving biological rhythms and neurophysiological activities to the brain. Since the early 1990s, rapid advances in molecular biology have enabled the identification of developmental genes, genes responsible for human congenital diseases, and relevant genes of mutant animals with various anomalies. In this review, we first look at the development of the eye, and we highlight seminal reports regarding archetypal gene defects underlying three developmental ocular disorders in humans: (1) holoprosencephaly (HPE), with cyclopia being exhibited in the most severe cases; (2) microphthalmia, anophthalmia, and coloboma (MAC) phenotypes; and (3) anterior segment dysgenesis (ASDG), known as Peters anomaly and its related disorders. The recently developed methods, such as next‐generation sequencing and genome editing techniques, have aided the discovery of gene mutations in congenital eye diseases and gene functions in normal eye development. Finally, we discuss Pax6 ‐genome edited mosaic eyes and propose that somatic mosaicism in developmental gene mutations should be considered a causal factor for variable phenotypes, sporadic cases, and de novo mutations in human developmental disorders.